Functional and Oncological Outcomes of Multidisciplinary Management of Ewing’s Sarcoma of Clavicle: A Single-Center Experience - Gulia, Ashish; Puri, Ajay; Gupta, Srinath; Vora, Tushar; Laskar, Siddhartha (South Asian Journal of Cancer, 2021)
Objectives Ewing’s sarcoma is best treated using a multidisciplinary approach. We discuss the functional and oncological outcomes of clavicular Ewing’s sarcoma which has been sparsely reported in literature.Materials and Methods We retrospectively evaluated patients who underwent resections for Ewing’s sarcoma of clavicle from January 2002 to December 2017. The study end points were locoregional recurrence free survival (LRFS), disease-free survival (DFS), and overall survival (OS) at 3 and 5 years, and functional outcomes measured by Musculoskeletal Tumor Society (MSTS) scores.Statistical Analysis The LRFS, DFS, and OS were calculated and analyzed using the Kaplan–Meier method and log-rank test.Results Data of 21 patients (male: 12, female: 9) was analyzed with a mean age [range] of 15.3 [6–40] years. Total clavicle excision was done in 62% (13 of 21) while 38% (n = 8) had partial resections. Radiotherapy was administered in 15 patients (71.5%). At a median follow-up of 42 months (range: 7–198), data of 20 patients was available for follow-up. Ten patients died (due to disease: nine, other reasons: One), eight are disease free and alive, one had metastasectomy on recurrence and is disease free and, one patient is alive with disease and on palliative chemotherapy. The LRFS, DFS, and OS were 95, 59, 65% and 95, 47, 59% at 3 and 5 years, respectively. The functional evaluation done for nine patients who are free of disease showed a mean MSTS score of 29 (range: 27–30; total clavicle excision: 28.5, partial clavicle excision: 29.5).Conclusion Patients with Ewing’s sarcoma of the clavicle who underwent resection without reconstruction have acceptable local control rates and excellent functional outcomes.
Keywords: clavicle; Ewing’s sarcoma; total clavicle excision; partial clavicle excision